Impact of letrozole supplementation during ovarian stimulation for fertility preservation in breast cancer patients - Charlotte Sonigo; Nathalie Sermondade; Jéremy Calvo; Julie Benard; Christophe Sifer; Michaël Grynberg (Elsevier, 2019)
Objectives: Oocyte and/or embryo vitrification after controlled ovarian stimulation (COS) represents the most established method of fertility preservation (FP) before cancer treatment. However, traditional COS regimens are associated with supraphysiologic serum estradiol and are therefore not recommended in estrogen-sensitive diseases such as breast cancer (BC). To protect the patients from the potential deleterious effects of elevated estrogen levels during COS for FP, protocols using aromatase inhibitors (letrozole) were developed. The present study aims at investigating whether COS with letrozole supplementation (COSTLES) modifies ovarian response in BC patients. Study design: One hundred and seventy-seven BC patients candidates for FP using oocyte and/or embryo vitrification following COS referred to our center between July 2013 and December 2016 were included in this retrospective case-control study. 94 patients underwent COSTLES while 83 had standard GnRH antagonist protocol. The number of oocytes retrieved, oocyte maturation rates, number of oocytes vitrified and follicle responsiveness to FSH assessed by the Follicular Output Rate (FORT) were assessed. Results: Women in both groups were comparable in terms of age and ovarian reserve tests leading to a similar number of oocyte recovered (13.1 ± 10.0 vs. 12.2 ± 8.0 oocytes, respectively, NS). However, oocyte maturation rates were significantly lower in COSTLES compared to standard protocol (64.9 ± 22.8 vs. 77.4 ± 19.3%, p < 0.001). As a result, the number of mature oocyte vitrified was lower in COSTLES group (7.8 ± 5.3 vs. 10.3 ± 8.5 oocytes, p < 0.001 respectively) Conclusion: Despite similar response to exogenous FSH, BC patients having undergone COSTLES show reduced oocyte maturation rates in comparison with those having received standard stimulation regimen. Keywords: Controlled ovarian stimulation, Breast cancer, Letrozole, Fertility preservation